2011
DOI: 10.3945/jn.110.136952
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Zinc Concentration Increases within 2 Weeks in Healthy Senegalese Men Given Liquid Supplemental Zinc, but Not Zinc-Fortified Wheat Bread

Abstract: The responsiveness of plasma zinc concentration to zinc fortification is uncertain. Our objective in this study was to determine whether plasma zinc concentration changes in response to consuming zinc-fortified foods or liquid zinc supplements. We conducted a 4-wk double-blind, randomized trial among 132 healthy Senegalese men ≥ 18 y. Participants received 1 of 4 interventions: 1) (control) 200 g/d of wheat bread fortified with iron and folic acid, but not zinc, and a liquid multivitamin supplement without zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Furthermore, the use of PDAs to collect these observations was challenging because of frequent malfunctions in the field, which resulted in some loss of data (corrupted files). Although the low level of observed supplement consumption is consistent with the level of change in PZC, this conclusion may only be valid for the group assigned to zinc tablets, because previous studies have found that PZC may not respond to additional zinc provided in food, despite the consistent positive response to supplements (Brown et al 2002Aaron et al 2011;Lo et al 2011).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, the use of PDAs to collect these observations was challenging because of frequent malfunctions in the field, which resulted in some loss of data (corrupted files). Although the low level of observed supplement consumption is consistent with the level of change in PZC, this conclusion may only be valid for the group assigned to zinc tablets, because previous studies have found that PZC may not respond to additional zinc provided in food, despite the consistent positive response to supplements (Brown et al 2002Aaron et al 2011;Lo et al 2011).…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, interactions with food and non‐linear dose–response relationships may influence the adherence estimates (Aaron et al . ; Lo et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that either one RDA is not enough to cover the zinc requirement of PLWH, or the concentration of plasma zinc does not reflect zinc status during fortification contrary to zinc supplementation. In our laboratory, we have demonstrated that plasma zinc concentration increased in children and adults who received daily zinc supplementation for a short time but not in those who received a zinc-fortified food containing a similar amount of zinc [24, 49]. Also, Mocchegiani et al showed that zinc supplementation with 3 times the RDA increases significantly the plasma zinc of PLWH [21].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review concluded that zinc added alone to foods may increase serum zinc, but zinc added with other micronutrients may have no effect on serum zinc (28). In controlled efficacy studies, plasma zinc did not respond to the consumption of zinc-fortified foods after 6 mo among children 6–8 mo of age in Peru (3 mg Zn/d) (29) and after 4 wk among men ≥18 y of age in Senegal (7.5 or 15 mg Zn/d) (30). However, serum zinc concentrations were greater after 24 and 36 mo among women in rural China whose families received wheat flour fortified with zinc and other nutrients than in women who received unfortified wheat flour (31).…”
Section: Discussionmentioning
confidence: 99%